学习汉语的动机分析——以高雅文化学院高中三年级为例 - Thedyus, Elva; Hendra, Agustina (Confucius Institute Universitas Sebelas Maret, 2024)
The need for motivation in learning activities is crucial and can be referred to as learning motivation. The presence of learning motivation in learning activities can make individuals more enthusiastic about learning something, whereas a lack of learning motivation makes the learning process difficult. Learning motivation can be classified into internal motivation and external motivation. Furthermore, learning motivation is influenced by various factors, including both internal and external motivations. The purpose of this study is to understand the motivation of third-year high school students at the Gaoya Cultural Academy to learn Chinese and to identify the factors influencing their motivation to learn Chinese. The research method used is descriptive qualitative methodology. Data collection techniques include literature review, questionnaire surveys, and interviews. The research findings indicate that the internal motivation of third-year high school students at the Gaoya Cultural Academy to learn Chinese is stronger than external motivation, although some students have less interest in learning Chinese. It can be observed that the most significant factor influencing the motivation of third-year high school students at the Gaoya Cultural Academy to learn Chinese is school-related factors (teachers), which are one of the external factors. Therefore, this study is expected to provide reference for enhancing students' motivation to learn Chinese.